2019
DOI: 10.3389/fpsyg.2019.01071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human, Relational, and Psychological Capitals on New Venture Performance

Abstract: Entrepreneurship research has been focusing on intangible capitals of an entrepreneur or entrepreneurial teams. Intellectual capital has been a useful framework for researching entrepreneurship, though the inclusion of intangible capital has not been comprehensive enough. We followed and extended this stream to add psychological capital into the discussion of the relationship between intellectual capital and new venture performance. We argue that psychological capital, human capital, and relational capital are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 50 publications
1
20
0
2
Order By: Relevance
“…In other words, the entrepreneurs are high in PC. Hmieleski found that entrepreneurs' PC could explain significantly variance in new venture performance, above and beyond measures of FC, HC, and SC (Hmieleski and Carr, 2008).…”
Section: Psychology Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the entrepreneurs are high in PC. Hmieleski found that entrepreneurs' PC could explain significantly variance in new venture performance, above and beyond measures of FC, HC, and SC (Hmieleski and Carr, 2008).…”
Section: Psychology Capitalmentioning
confidence: 99%
“…For most entrepreneurs, PC is the important factor determining the entrepreneurship. Most entrepreneurs regularly confront the shortages of financial, human, and SC, and they have only themselves and their psychological state to rely on to get the job done (Hmieleski and Carr, 2008). The PC, especially hope and self-efficacy can promote entrepreneurial passion, which is a driver and source of energy to work hard and persist in the process (Baum and Locke, 2004).…”
Section: Mediating Roles Of Traditional Entrepreneurial Capitals On Pmentioning
confidence: 99%
“…For Luthans and Youssef-Morgan (2017), these aforementioned psychological capacities were the first to be incorporated into PsyCap because of certain criteria, such as adequacy to theory, measurement, development, and impact on performance. These four psychological capabilities together enable an individual to overcome obstacles and remain motivated to achieve goals and success (Harms et al, 2018;Wang et al, 2019).…”
Section: Positive Psychological Capitalmentioning
confidence: 99%
“…At the same time, reliable social networks have the function to enhance those emotional competences related to psychological capital (Fredrickson and Levenson, 1998). Recently, Wang et al (2019) found out a bidirectional relation among psychological capital and what they address as relational capital. In a qualitative research they carried out about the "effect of human, relational, psychological capital on new venture performance, " the authors found out not only that some components of psychological capital fostered the establishment of resourceful networks but also that some horizontal and vertical relationships nurtured entrepreneurs' psychological capital.…”
Section: Case Studymentioning
confidence: 99%